The Impact of Energy Transition on Socio-Economic Issues: Evidence from Vietnam - Viet, Nguyen Vu; Lien, Vu Thi Phuong; Duy, Do Dinh (Journal of Ecohumanism, 2025)
This study analyzes the impact of energy transition on socio-economic issues in Vietnam. By combining qualitative and quantitative research methods during the 2015-2023 period, the study demonstrates that energy transition is an inevitable trend that brings multiple economic, social, and environmental benefits to Vietnam, with positive impacts such as promoting economic growth, creating new jobs, enhancing energy security, and improving environmental conditions and public health. However, this process also presents challenges in terms of investment costs, technology, and human resources. Quantitative analysis results show that in the short term, energy transition has not yet shown clear positive effects on economic growth, but has contributed to reducing poverty rates and improving average life expectancy. The study proposes comprehensive solutions regarding policy, finance, technology, and raising community awareness to promote fair and sustainable energy transition in Vietnam, aiming towards the net-zero emissions target by 2050.